The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1073/pnas.1207210109
|View full text |Cite
|
Sign up to set email alerts
|

Tmem100 , an ALK1 receptor signaling-dependent gene essential for arterial endothelium differentiation and vascular morphogenesis

Abstract: Members of the transforming growth factor-β superfamily play essential roles in various aspects of embryonic development and physiological organ function. Among them, bone morphogenetic protein (BMP) 9 and BMP10 regulate embryonic vascular development by activating their endothelial receptor ALK1 (activin receptor-like kinase 1, also called Acvrl1). ALK1-mediated intracellular signaling is implicated in the etiologies of human diseases, but their downstream functional proteins are largely unknown. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 91 publications
(129 citation statements)
references
References 32 publications
10
118
0
Order By: Relevance
“…As we previously reported (Somekawa et al, 2012), all Tmem100 null embryos died before E11.0 in the present study. They started to show abnormal cardiac morphology from E9.5 ( Fig.…”
Section: Defects Of Endmt During Avc Cushion Formation In Tmem100 Nulsupporting
confidence: 88%
See 3 more Smart Citations
“…As we previously reported (Somekawa et al, 2012), all Tmem100 null embryos died before E11.0 in the present study. They started to show abnormal cardiac morphology from E9.5 ( Fig.…”
Section: Defects Of Endmt During Avc Cushion Formation In Tmem100 Nulsupporting
confidence: 88%
“…In addition, previous studies demonstrated Tmem100 expression not only in the embryonic heart and vasculature but also in the adult lung, prostate, kidney, and enteric neurons in humans or mice (van der Heul-Nieuwenhuijsen et al, 2006;Georgas et al, 2009;Moon et al, 2010;Somekawa et al, 2012;Eisenman et al, 2013). Studying Tmem100 actions in various organs will help find a new module of cellular signaling not only in cardiovascular development but also in other biological processes.…”
Section: Developmental Dynamicsmentioning
confidence: 96%
See 2 more Smart Citations
“…Tmem100, also changed in our screen, is downstream of Bmp10 and is required in arterial endothelium. 43 Taken together, the human genetic and mouse genetic evidence implicate the transcription factor HIC2 as a contributor to the atypical 22q11DS phenotype. However, we do not discount the possibility of a combined haploinsufficiency of HIC2 with any or all of TBX1, CRKL, and MAPK1, depending on the size of the deletion.…”
Section: D-22q11ds Most Commonly Results From Deletions With a Proximmentioning
confidence: 99%